2007
DOI: 10.1007/s00192-007-0443-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequential hydrodistension and intravesical instillation of hyaluronic acid under general anaesthesia for treatment of refractory interstitial cystitis: a pilot study

Abstract: Pilot study looking at the combination of general anaesthetic hydrodistension and intravesical hyaluronic acid for treatment of refractory interstitial cystitis. Twenty-three treatment refractory patients were recruited with an average age 53.4 years. All underwent general anaesthetic cystoscopy, hydrodistension and instillation of hyaluronic acid (40 mg/50 ml). The bladder was then subsequently drained with the patient awake. Two initial treatments were carried out a month apart and duration between treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Leppilahti et al reported complete or partial response in eight patients out of 12 with this technique [22]. Ahmad et al recently reported their experience on 23 patients: they obtained a response rate of 74% with an average follow up of 15.8 months [24]. In a different study, HA was used in combination with CS, another component of the GAG layer, which was administered systemically with promising results in patients with refractory PBS/IC.…”
Section: Discussionmentioning
confidence: 99%
“…Leppilahti et al reported complete or partial response in eight patients out of 12 with this technique [22]. Ahmad et al recently reported their experience on 23 patients: they obtained a response rate of 74% with an average follow up of 15.8 months [24]. In a different study, HA was used in combination with CS, another component of the GAG layer, which was administered systemically with promising results in patients with refractory PBS/IC.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrodistension with and without instillation additives has been shown to be an effective therapeutic procedure for IC/BPS and is generally a safe procedure other than rare reports of bladder rupture. [162][163][164] However, relief of symptoms from hydrodistension therapy has been shown to decline over the time scale of months, with a wide variation in efficacy thought to be partly due to many different practices for hydrodistention. 19,80,165,166 Greater duration of therapy has been found in patients with ulcerative IC/PBS and in patients without comorbidities such as IBS.…”
Section: Treatmentmentioning
confidence: 99%
“…Ahmad and colleagues and Shao and colleagues used 40 mg HA administered intravesically to prolong the bladder capacity obtained after BH [Shao et al 2010;Ahmad et al 2008]. They observed in each study an improvement in mean bladder capacity; 492 ml versus 776 ml after 16 months of follow up in the 23 patients [Ahmad et al 2008]; þ27 ml versus À5 ml in the placebo group after 6 months [Shao et al 2010]. …”
Section: Pbs/icmentioning
confidence: 99%